2017
DOI: 10.1007/s00122-017-2895-3
|View full text |Cite
|
Sign up to set email alerts
|

Exome sequence genotype imputation in globally diverse hexaploid wheat accessions

Abstract: Imputing genotypes from the 90K SNP chip to exome sequence in wheat was moderately accurate. We investigated the factors that affect imputation and propose several strategies to improve accuracy. Imputing genetic marker genotypes from low to high density has been proposed as a cost-effective strategy to increase the power of downstream analyses (e.g. genome-wide association studies and genomic prediction) for a given budget. However, imputation is often imperfect and its accuracy depends on several factors. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 37 publications
1
11
0
Order By: Relevance
“…We have shown that the accuracy of imputation was > 0.71. This level of accuracy is similar to what has been previously achieved in other crops 54 . However, it is substantially less than in human and other mammals 56 58 .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…We have shown that the accuracy of imputation was > 0.71. This level of accuracy is similar to what has been previously achieved in other crops 54 . However, it is substantially less than in human and other mammals 56 58 .…”
Section: Discussionsupporting
confidence: 89%
“…Imputation has been implemented in several crops, a study by Torkamaneh et al 53 achieved high accuracy when imputing from low-coverage genotyping-by-sequencing (GBS) to WGS in soybean. Similarly, Shi et al 54 examined the potential of exome sequence imputation in wheat. These studies emphasized the need to carefully evaluate imputation algorithms in new datasets as large differences in performance exist.…”
mentioning
confidence: 99%
“…Of the 633 samples genotyped using the GBS-t method, 149 samples were processed for WGR, including one biological replicate ( Supplementary Table S1 and Supplementary Figure S1 ). This included 10 samples comprising both Australian spring types and diverse winter types that were used in experimental development of WGR library preparation, 6 commonly studied European winter types, 87 significant Australian spring types, and 46 samples forming a global diversity panel chosen using a custom pipeline, selecting a representative of each branch clade from a neighbor-joining (NJ) tree, to capture overall diversity ( Shi et al, 2017 ).…”
Section: Methodsmentioning
confidence: 99%
“…Imputation approaches can also be applied to impute whole genomes from SNP arrays using haplotype and pedigree information (Das et al ., ). Although the Brassica 60K and wheat 90K markers are not dense enough to impute whole genomes, imputing from 9 to 90K SNP density in wheat was possible at 70% accuracy with 197 reference samples (Shi et al ., ). CropSNPdb markers can therefore be used as references to impute Brassica 60K and wheat 90K markers from lower density marker sets.…”
Section: Discussionmentioning
confidence: 97%